Prevalence and Factors Associated with Neonatal Death among Neonates referred to Neonatal Intensive Care Unit from an Urban high-density community of Lusaka, Zambia - Napanje, Chomba; Sampa, Mutale; Makasa, Musonda; Jacobs, Choolwe (Insights in Public Health Journal, 2024)
Background: The first month of life is the most vulnerable period of child survival. Globally the neonatal period accounted for nearly half (47 per cent) of all under-five deaths that occurred in 2022. Factors associated with neonatal death vary between environments and are essentially not well understood. This study aimed to investigate the prevalence and factors associated with neonatal death among neonates born at Kanyama first level hospital, located in an urban high-density community and referred to University Teaching Hospital (UTH)- Neonatal Intensive Care Unit (NICU). Methods: A cross-sectional study was conducted in January and February 2023 through data extraction from registers and medical files on prevalence and factors associated with neonatal death. Pearson’s Chi square, fisher’s exact test and multiple logistic regression were conducted using the STATA version 14.2. 205 medical records were selected for the study using Cochrane (1963) formula to calculate a minimum sample size of 104. Results: The study population comprised neonates born at Kanyama first level hospital in 2021 and 2022 of which 38.05% were female, 61.95% were male, 60% were born at full term and 40% were born at pre-term. Factors associated with neonatal death were labour complications (AOR: 3.46, p=0.039), conditions requiring special attention such as preeclampsia (AOR: 20.4, p=0.001), concerning Apgar score at one minute (AOR=4.50, p=0.014) and pre-term at birth (AOR=7.50, p<0.0001). Conclusion: The prevalence of neonatal death was found to be high and the associated factors included; labour complications, condition requiring special attention, Apgar score at one minute and term at birth. Therefore, neonatal survival should be prioritized through pregnancy monitoring, quality antenatal and Emergency Obstetric and Neonatal Care (EmONC) training to improve response interventions in the event of complications. Keywords: neonatal mortality, urban high-density community, factors associated, neonatal intensive care unit